Pengaruh Investment Opportunity Set dan Ukuran Perusahaan Terhadap Hubungan Antara Free Cash Flow dengan Kebijakan Hutan - Marfuah - (Jurnal Aplikasi Bisnis, 2016)
The main purpose of this study is to empirically examine the moderating effect of Investment Opportunity Set (ICS) and company size on the relationship between free cash flow to debt policy. The test results of the 159 samples were selected for sampling purposed the observation period 2006 to 2011 managed to support the first hypothesis which states that firms with lower ICS, free cash flow has a positive relationship with debt policy and the second hypothesis that the large companies, free cash flow has a positive relationship with debt policy. Tests on the three independent variables that allegedly could be used to reduce agency cost, the managerial ownership variables, the dividend payout ratio, and institutional ownership showed no significant results. While ROA as a control variable in this study showed a significant negative effect on the debt. This indicates that the greater the company's ability to generate profits, the company is likely to reduce its debt, as more internal funds available for investment company. The results of this study useful for investors to understand the behavior of corporate management in Indonesia in managing free cash flow is usually a conflict between shareholders and managers of the company. On companies with low levels of ICS, the management company will tend to increase the debt when the company generated free cash flow is high. Free cash flow problems are also more pronounced in the large company; the company's management will tend to increase the debt when the company generated free cash flow is high. Thus investors should consider the variable growth opportunities and the size of the company if the company will invest in companies with high free cash flow.